Pour de nouvelles rencontres en Pays de Caux - Boris Menguy (Projets de Paysage)
Although planning makes it possible to express political intentions and provide safeguards against certain excesses, it does sometimes fail to protect us from divisions caused by land zoning. Administrative limits often make no sense and are inappropriate for ensuring profitable use of land space or guaranteeing the quality of the landscape. In 2014, a workshop organised by the urban planning agency of the region of Le Havre and the Seine estuary area focused on this question and made it possible to develop, with the valuable contributions of three fourth year students from the Ecole national supérieur du paysage (ENSP), approximately one hundred original proposals for fringe areas belonging to five landscape entities included in the master urban plan for the Le Havre Pointe de Caux estuary area. The article refers to expectations in terms of the attractiveness of the area, describes the co-design approach for generating the proposals and focuses on the questions raised by the north-western fringe of the Le Havre, a key suburban area the development of which presents new prospects for the future. Can redesigning these fringe areas contribute to defining new spaces and developing new practises ?